MEDIA INFORMASI PENGAJIAN MAJLIS TAKLIM DI KECAMATAN KERTAJATI BERBASIS WEB - salahuddin nurul fahmi (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2022)
Media Information in general is a tool for collecting and rearranging information so that it becomes useful material for recipients of information. Majelis taklim is one of the non-formal diniyah educational institutions that aims to increase faith and piety to Allah SWT and noble character for its congregations, as well as to realize mercy for the universe. Majlis taklim recitations are often held in the Kertajati sub-district, but many people in Kertajati do not know the schedule for the recitation of the Majlis because the delivery is only by word of mouth, therefore the impact of ignorance is only the people around the recitation place who follow it so that the presence of the congregation 'ah not optimal. So that the Information Media for the Majlis Taklim Recitation was made. With this system, it is expected to provide an online recitation schedule information feature, which can make it easier for the public to find the location of the recitation to be held. This system is made using CodeIgniter while for system development using the Waterfall Method. Keywords : Information Media, Majlis Taklim, Recitation, CodeIgniter, Waterfall.